Human Rights Violations and Corporate Criminal Liability: An Analysis of the New Indonesian Criminal Law - Mia Amiati; Adhryansah Adhryansah; Iman Prihandono (Sriwijaya Law Review, 2024)
In light of the increasing role of corporations in facilitating gross human rights violations, this article seeks to evaluate the implementation of the Indonesian Criminal Law in addressing corporate criminal liability. Notably, the recently amended Indonesian Criminal Law recognizes corporations as subjects of criminal law, but Law No. 26 of 2000, which regulates gross human rights violations, does not. Consequently, this research specifically scrutinizes the Indonesian Criminal Code, Law No. 26 of 2000, and international legal standards to answer the issues: rules of aiding and abetting under international criminal law and the applicability of corporate culture theory, and the implementation of Indonesian Criminal Law in addressing corporate criminal liability for gross human rights violations. Examining these issues relies on three methodologies, namely the statutory approach, conceptual approach, and case approach. The results of this article uncover that the recognition of corporations as subjects under the new Indonesian Criminal Code and rectification of the ratione materiae of Law No. 26 of 2000 open the avenue for corporations to be held criminally liable for gross human rights violations based on aiding and abetting. Furthermore, the theory of corporate culture envisaged in the new Indonesian Criminal Code renders the plausibility of holding corporations liable if they are deemed to cultivate a culture that pushes or encourages a gross human rights violation.